2013
DOI: 10.1021/cm402384j
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Noble Metal Nanocrystal Growth: The Role of Halides

Abstract: Anisotropic (nonspherical) metal nanoparticles are of widespread research interest because changing the shape of metals at the nanoscale can provide access to materials with unique optical, electronic, and catalytic properties. The development of seeded growth syntheses has provided researchers unprecedented access to anisotropic metal nanocrystals (particularly, gold, silver, platinum, and palladium nanocrystals) with precisely controlled dimensions and crystallographic features. The mechanisms by which the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
295
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(314 citation statements)
references
References 90 publications
8
295
0
4
Order By: Relevance
“…Reagent mixtures are typically purchased from distributors without full disclosure of the constituent chemicals and those mixtures can further undergo a multitude of reactions to generate new species. Without knowledge of what chemical species are present, researchers cannot understand the mechanistic underpinnings of these systems or control their uniformity (15,19,20,(34)(35)(36). For semiconductor metal chalcogenides, many key advances have been made with the solvent tri-N-octylphosphine oxide (TOPO).…”
Section: From Atoms To Crystalline Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reagent mixtures are typically purchased from distributors without full disclosure of the constituent chemicals and those mixtures can further undergo a multitude of reactions to generate new species. Without knowledge of what chemical species are present, researchers cannot understand the mechanistic underpinnings of these systems or control their uniformity (15,19,20,(34)(35)(36). For semiconductor metal chalcogenides, many key advances have been made with the solvent tri-N-octylphosphine oxide (TOPO).…”
Section: From Atoms To Crystalline Nanoparticlesmentioning
confidence: 99%
“…Subsequent research instead showed that phosphonates and phosphonic acids present in or produced at high temperatures coordinate stronger than TOPO and dictate the reaction pathway (21,34). Similarly, halide impurities in ubiquitously used surfactants for noble metal nanoparticle syntheses [e.g., cetyltrimethylammonium bromide (CTAB)] went unidentified for almost a decade of research (17,19,35,36). Only after extensive efforts to identify, purify, and systematically dope in halides were researchers able to reproducibly synthesize nanostructures with controlled shape (17-19, 35, 36).…”
Section: From Atoms To Crystalline Nanoparticlesmentioning
confidence: 99%
“…Slower growth of {110} side faces and faster growth of {100} end facets results in a breaking of the growth symmetry and adjustment of the final anisotropic shape [30]. The growth rate between the Au{110} and Au{100} facets of the f.c.c (face-centred close-packed) Au structure can be simply attuned by varying the Ag ion concentration.…”
Section: Underpotential Deposition (Upd): the Silver Ions Cause Undermentioning
confidence: 99%
“…They have been, for instance, used to stain porcelain and also church windows [1], and today gold nanoparticles (GNPs) find uses as active components in such diverse applications as solar cells [2][3][4], biological and medical treatments [5,6], sensing [7], optical data storage8 and surface-enhanced Raman spectroscopy (SERS) [9,10]. In recent years a number of different geometries other than spheres have gained prominence as may clearly be seen from examining the many examples present in the literature [11,12]. With the exception of spheres the most prominently studied geometric form is that of rods, the synthetic methodology for which has been developed by El-Sayed et al [13] and which has recently been further advanced by Murray et al [11].…”
Section: Introductionmentioning
confidence: 99%